Myosin Activator Omecamtiv Mecarbil Increases Myocardial Oxygen Consumption and Impairs Cardiac Efficiency Mediated by Resting Myosin ATPase Activity. (July 2015) - Bakkehaug, Jens Petter; Kildal, Anders Benjamin; Engstad, Erik Torgersen; Boardman, Neoma; Næsheim, Torvind; Rønning, Leif; Aasum, Ellen; Larsen, Terje Steinar; Myrmel, Truls; How, Ole-Jakob
<x xml:space="preserve">Abstract</x> Background— Omecamtiv mecarbil (OM) is a novel inotropic agent that prolongs systolic ejection time and increases ejection fraction through myosin ATPase activation. We hypothesized that a potentially favorable energetic effect of unloading the left ventricle, and thus reduction of wall stress, could be counteracted by the prolonged contraction time and ATP-consumption. Methods and Results— Postischemic left ventricular dysfunction was created by repetitive left coronary occlusions in 7 pigs (7 healthy pigs also included). In both groups, systolic ejection time and ejection fraction increased after OM (0.75 mg/kg loading for 10 minutes, followed by 0.5 mg/kg/min continuous infusion). Cardiac efficiency was assessed by relating myocardial oxygen consumption to the cardiac work indices, stroke work, and pressure–volume area. To circumvent potential neurohumoral reflexes, cardiac efficiency was additionally assessed in ex vivo mouse hearts and isolated myocardial mitochondria. OM impaired cardiac efficiency; there was a 31% and 23% increase in unloaded myocardial oxygen consumption in healthy and postischemic pigs, respectively. Also, the oxygen cost of the contractile function was increased by 63% and 46% in healthy and postischemic pigs, respectively. The increased unloaded myocardial oxygen consumption was confirmed in OM-treated mouse hearts and explained by an increased basal metabolic rate. Adding the myosin ATPase inhibitor, 2, 3-butanedione monoxide abolished all surplus myocardial oxygen consumption in the OM-treated hearts. Conclusions— Omecamtiv mecarbil, in a clinically relevant model, led to a significant myocardial oxygen wastage related to both the contractile and noncontractile function. This was mediated by that OM induces a continuous activation in resting myosin ATPase.